2014
DOI: 10.1103/physreve.89.013009
|View full text |Cite
|
Sign up to set email alerts
|

Free turbulent shear layer in a point vortex gas as a problem in nonequilibrium statistical mechanics

Abstract: This paper attempts to unravel any relations that may exist between turbulent shear flows and statistical mechanics through a detailed numerical investigation in the simplest case where both can be well defined. The flow considered for the purpose is the two-dimensional (2D) temporal free shear layer with a velocity difference ΔU across it, statistically homogeneous in the streamwise direction (x) and evolving from a plane vortex sheet in the direction normal to it (y) in a periodic-in-x domain L×±∞. Extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Perturbing the initial vortex-sheet with random "errors" of decreasing magnitude and simultaneously decreasing the viscosity ν, the crucial "forgetting" of initial error v(0) − v (0) was observed in Figure 1 of [22] for the mean-square separation v(t) − v (t) 2 after a sufficient time-interval. Furthermore, after this initial short transient, the spontaneously stochastic ensemble of solutions entered a selfsimilar growth phase with universal statistical properties independent of regularization and noise level, consistent with earlier observations [44].…”
Section: Review Of Current Evidence For Spontaneous Stochasticitysupporting
confidence: 88%
See 1 more Smart Citation
“…Perturbing the initial vortex-sheet with random "errors" of decreasing magnitude and simultaneously decreasing the viscosity ν, the crucial "forgetting" of initial error v(0) − v (0) was observed in Figure 1 of [22] for the mean-square separation v(t) − v (t) 2 after a sufficient time-interval. Furthermore, after this initial short transient, the spontaneously stochastic ensemble of solutions entered a selfsimilar growth phase with universal statistical properties independent of regularization and noise level, consistent with earlier observations [44].…”
Section: Review Of Current Evidence For Spontaneous Stochasticitysupporting
confidence: 88%
“…A simple Lagrangian manifestation of spontaneous stochasticity is the universal Richardson t 3 -growth in mean-square width of plumes of smoke or of other aerosols advected by a turbulent flow [5], which many observations suggest to be independent of the details of the source and of the mass diffusivity of the aerosol ([42], section 24.3). More recently, it has been argued [22] that Eulerian spontaneous stochasticity explains how universal statistics are attained in a finite time for turbulent mixing layers during their phase of non-stationary, selfsimilar "equilibrium" spread [43,44]. In addition to many hints and indirect pieces of evidence for spontaneous stochasticity, there are a few controlled, precision studies which provide direct corroboration of the phenomenon.…”
Section: Review Of Current Evidence For Spontaneous Stochasticitymentioning
confidence: 99%
“…Beale & Majda 24 , Marchioro & Pulvirenti 25 ) that prove the convergence of the vortexgas to weak solutions of the Euler equations under appropriate limits (see refs. 12,19 for further discussion). The use of the point-vortex approximation has a long history which includes the early work of Rosenhead 26 and subsequently of Hama and Burke 27 , Acton 28 , Delcourt & Brown 29 , Aref & Siggia 30 and others.…”
Section: Computational Setupmentioning
confidence: 99%
“…Extensive simulations (using the vortex-gas model, to be described in detail in Sec. 2) of a 2D temporally evolving free shear layer by Suryanarayanan, Narasimha and Hari Dass 19 (SNH henceforth) have provided new insights. In this work, it was shown that a temporally evolving free shear layer in a gas of point vortices, in a streamwise periodic domain L, exhibits three distinct regimes.…”
Section: Introductionmentioning
confidence: 99%
“…The point vortex model, originally developed by Kirchoff [1] as a limiting form of Euler's equations in two dimensions, continues to provide a conceptual and computational tool for understanding inviscid, nonlinear vortex dynamics in both traditional and superfluid turbulence [2][3][4]. The multibody Hamiltonian describing the dynamics of idealized point vortices serves as a paradigm for developing kinetic theories in systems dominated by long-range interactions [5,6].…”
Section: Introductionmentioning
confidence: 99%